New Metropolitan Perspectives Knowledge Dynamics, Innovation-driven Policies Towards the Territories' Attractiveness Volume 1 - Bevilacqua, Carmelina; Calabrò, Francesco; Della Spina, Lucia (Smart Innovation, Systems and Technologies, 2020)
This open access book presents the outcomes of the symposium "NEW METROPOLITAN PERSPECTIVES," held at Mediterranea University, Reggio Calabria, Italy on May 26-28, 2020. Addressing the challenge of Knowledge Dynamics and Innovation-driven Policies Towards Urban and Regional Transition, the book presents a multi-disciplinary debate on the new frontiers of strategic and spatial planning, economic programs and decision support tools in connection with urban-rural area networks and metropolitan centers. The respective papers focus on six major tracks: Innovation dynamics, smart cities and ICT; Urban regeneration, community-led practices and PPP; Local development, inland and urban areas in territorial cohesion strategies; Mobility, accessibility and infrastructures; Heritage, landscape and identity;and Risk management,environment and energy. The book also includes a Special Section on Rhegion United Nations 2020-2030. Given its scope, the book will benefit all researchers, practitioners and policymakers interested in issues concerning metropolitan and marginal areas.